Bridging Educational Gaps: Implementing Solution-Driven Methods in History Learning at a Peripheral School in Jember - Eka Yuliana Rahman; Amri Dhimas Maulana (Journal Education Innovation (JEI), 2025)
This research examines the implementation of solution-driven methods in learning history at SMAN 1 Tanggul, a school in the peripheral area of Jember Regency, to bridge the existing educational gap. The main objectives of this research are to identify the effectiveness of solution-driven method in improving students' understanding and engagement as well as to identify the challenges and successes in its implementation. This research method uses qualitative with a case study approach. Data were collected through in-depth interviews with history teachers and students, classroom observations, and analyses of relevant documents, such as lesson plans and student activity records. Data analysis was conducted using thematic analysis techniques to identify patterns and main themes related to the implementation of solution-driven methods. The results showed that the solution-driven method significantly increased students' engagement in history learning by linking the subject matter to their real-life situations. Students showed an increased understanding of the historical context and the relevance of historical events in their daily lives. In addition, this approach helped improve students' learning motivation and analytical skills. Overall, the results of this study suggest that the solution-driven method can be an effective tool to address the education gap in peripheral schools such as SMAN 1 Tanggul.